Increased pain sensitivity and pain-related anxiety in individuals with autism - Failla, Michelle D.; Gerdes, Madison B.; Williams, Zachary J.; Moore, David J.; Cascio, Carissa J. (Pain reports, 2020)
Individuals with autism spectrum disorder (ASD) often exhibit differences in pain responsivity. This altered responsivity could be related to ASD-related social communication difficulties, sensory differences, or altered processing of pain stimuli. Previous neuroimaging work suggests altered pain evaluation could contribute to pain-related anxiety in ASD. We hypothesized that individuals with ASD would report increased pain sensitivity and endorse more pain-related anxiety, compared to typically developing controls. We recruited 43 adults (ASD, n = 24; typically developing, n = 19) for 3 heat pain tasks (applied to the calf). We measured heat pain thresholds using a method of limits approach, a pain-rating curve (7 temperatures between 40 and 48°C, 5 seconds, 5 trials each), and a sustained heat pain task with alternating low (42°C) and high (46°C) temperatures (21 seconds, 6 trials each). Individual differences in pain-related anxiety, fear of pain, situational pain catastrophizing, depressive symptoms, and autism-related social communication were assessed by self-report. There were no group differences in pain thresholds. For suprathreshold tasks, mean pain ratings were higher in ASD across both the pain-rating curve and the sustained heat pain tasks, but responses in the ASD group were more varied. Pain anxiety (PASS-Total) and pain-related fear (FOP-III-Total) were higher in the ASD group and were positively associated with pain ratings. Our results suggest that both sensory and cognitive experiences of pain are heightened and interact reciprocally in adults with ASD. Future studies are needed to evaluate the impact of pain-related anxiety on treatment-seeking and pain behaviors, given higher levels of pain-related anxiety in ASD.